2022
DOI: 10.5219/1760
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of internal organs and additive tissue of hybrid hypophthalmichthys (Hypophthalmichthys spp.) as a promising raw material for the production of dietary nutritional products

Abstract: Preservation of the nutritional value of fish and the useful qualities of its rich composition is extremely important. The urgent task of the food industry is to develop and create quality food products that meet modern production trends and compete in domestic and foreign markets. This scientific paper describes studies aimed at assessing the specific weight (%) of essential nutrients (glycogen, proteins, and lipids) in particular organs and tissues of different size and mass groups of the hybrid of silver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The average lipids values in most organs and tissues of biennials of the hybrid of silver and bighead carp caught from winter ponds in 2019, biennials, were at 1% and below. The results of the biennials of the hybrid of silver and bighead carp in 2019 indicate that their physiological state at the time of the study was within the physiological norm [42].…”
Section: Institute Of Fisheries 'Nyvka' Of the National Academy Of Ag...mentioning
confidence: 87%
See 4 more Smart Citations
“…The average lipids values in most organs and tissues of biennials of the hybrid of silver and bighead carp caught from winter ponds in 2019, biennials, were at 1% and below. The results of the biennials of the hybrid of silver and bighead carp in 2019 indicate that their physiological state at the time of the study was within the physiological norm [42].…”
Section: Institute Of Fisheries 'Nyvka' Of the National Academy Of Ag...mentioning
confidence: 87%
“…Thus, according to the results of studies conducted in 2018, it was found that concentration of glycogen, total protein, and lipids in fish organs and tissues of fish from SEEF "Nyvka" IF NAAS and TRPLF NULES of Ukraine was satisfactory. The results indicate that the young-of-the-year hybrid of silver and bighead carp in the winter significantly reduces or stops the trophic activity and switches partially or completely to endogenous nutrition [42].…”
Section: Institute Of Fisheries 'Nyvka' Of the National Academy Of Ag...mentioning
confidence: 92%
See 3 more Smart Citations